Oral Manifestations of Exudative Erythema Multiforme in a Patient with COVID-19 - Zana Sllamniku Dalipi; Fatmir Dragidella; Donika Kastrati Dragidella (Case Reports in Dentistry)
Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is a viral infection with multiorgan manifestations that may affect the oral mucosa. The full range of oral manifestations of COVID-19 are unknown, and there are limited reports describing the features of oral manifestations of COVID-19, including taste loss, oral lesions, and xerostomia. The aim of this study is to report a case of oral erythema multiforme (EM) manifesting as oral, lip, and skin lesions in a COVID-19 patient. The presence of oral lesions in the late stage of COVID-19 could be related to weak patient immunity or related therapies.